2016
DOI: 10.1111/petr.12727
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors of bacterial infections in children following autologous hematopoietic stem cell transplantation: Single‐center experience from Jordan

Abstract: Bacterial infection is a serious sequela following AHSCT; however, limited data are available regarding pediatric recipients, especially in developing countries. We retrospectively analyzed the incidence and risk factors of bacterial infections during the first 100 days after AHSCT in children at KHCC in Amman, Jordan between January, 2005 and September, 2013. A total of 65 patients were identified, with median age of four yr (1-17). Forty-seven patients (72.3%) had solid tumors and 18 (27.7%) had lymphoma. Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…A study conducted in Johannesburg investigating infections from 1991 to 1995 documented a CFR of 8.5%, whereas a recent study conducted in Qatar over a study period of 2004 to 2011 recorded a CFR of 2.2% (Van de Wetering et al, 2001;Al-Mulla et al, 2014). Furthermore, a study of infectious complications in children with AML and Down syndrome reported no deaths from bacterial or fungal infections (Hussein et al, 2016). The low mortality at RCWMCH may reflect an aggressive approach to monitoring BSI in oncology patients, lower resistance rates of microbial isolates, and the short median time to initiating effective antimicrobial therapy of 0 days.…”
Section: Discussionmentioning
confidence: 96%
“…A study conducted in Johannesburg investigating infections from 1991 to 1995 documented a CFR of 8.5%, whereas a recent study conducted in Qatar over a study period of 2004 to 2011 recorded a CFR of 2.2% (Van de Wetering et al, 2001;Al-Mulla et al, 2014). Furthermore, a study of infectious complications in children with AML and Down syndrome reported no deaths from bacterial or fungal infections (Hussein et al, 2016). The low mortality at RCWMCH may reflect an aggressive approach to monitoring BSI in oncology patients, lower resistance rates of microbial isolates, and the short median time to initiating effective antimicrobial therapy of 0 days.…”
Section: Discussionmentioning
confidence: 96%
“…This may be attributed to the intense myeloand immunosuppression caused by the HSCT preparative regimen, which leads to the development of disease by otherwise less virulent microorganisms. In a retrospective study, Hussein et al 10 were the most commonly observed. A national study also showed a similar proportion of GNB (46.8%), but coagulase-negative staphylococci were the most prevalent.…”
Section: Discussionmentioning
confidence: 98%
“…17 Invasive fungal disease by Aspergillus is said to be proven when: (i) the presence of hyphae is associated with evidence of tissue invasion observed on histopathological, cytopathological, or microscopic examination of a specimen obtained by aspiration or biopsy; (ii) there is recovery of filamentous fungi in a culture specimen obtained from a sterile site, associated with clinical or radiological changes consistent with an infectious process. 18 An institutional statistical software package designed by our local HICC for epidemiological surveillance was used for the study data- Median age in years (IQ25%-75%) 10 The same patient may have used more than one catheter at a time.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations